Cystic Glioblastoma: An Evaluation of IDH1 Status and Prognosis. Issue 1 (1st October 2013) - Sarmiento, J. Manuel; Nuño, Miriam; Ortega, Alicia; Mukherjee, Debraj; Fan, Xuemo; Black, Keith L.; Patil, Chirag G.
Abstract: BACKGROUND: Controversy exists regarding the prognostic significance of cystic features in newly diagnosed glioblastoma multiforme (GBM) and the pathological origin of cystic GBMs. OBJECTIVE: To determine whether cystic GBMs develop from low-grade gliomas by evaluating IDH1 status and to evaluate the differences in overall survival between patients with cystic and noncystic tumors. METHODS: We retrospectively reviewed the records of 351 consecutive newly diagnosed adult GBM patients treated at our institution from October 1997 to November 2011; patients with >50% cystic tumor composition were further identified. IDH1 mutation was determined by immunohistochemical staining. Patient characteristics and treatment were reported for cystic and noncystic tumors separately. Overall survival was reported for cystic and noncystic cohorts by using the Kaplan-Meier estimates. RESULTS: Of 351 patients, 27 (7.7%) had cystic tumors and 324 (92.3%) had noncystic tumors. Tumor samples for patients with cystic GBMs were immunohistochemically analyzed for IDH1 mutations. Two (7.4%) of the 27 tumor samples were documented as having IDH1 mutations. Characteristics such as age, sex, perioperative Karnofsky Performance Status, tumor size, extent of resection, postsurgery radiation, and temozolomide therapy were comparable in the and noncystic cohorts. Patients in the cystic cohort had a median overall survival of 15.0 months compared with 18.2 months for the noncystic cohort (log-rank P = .77). CONCLUSION: The low frequency of IDH1 mutation status in our cystic cohort strongly suggests that most newly diagnosed cystic GBMs do not arise from malignant transformation of previously undiagnosed low-grade gliomas. Furthermore, there is no difference in overall survival between patients newly diagnosed with cystic and noncystic GBMs.